Pengaruh Faktor Fundamental Dan Faktor Teknikal Terhadap Harga Saham (Studi Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019) - Niken Cahyani Agungtya; Budi Wahono; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study is to determine and analyze the influence of Fundamental Factors and Technical Factors on Stock Prices (Studies in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2019. The population in this study is the food and beverage sub-sector companies which 26 companies listed on the Indonesia Stock Exchange in 2016-2019. The sample used was 12 companies in the food and beverage sub-sector. The sampling technique used purposive sampling. Data analysis used multiple regression analysis. Based on the results of the study it is known that ROA, DER, CR and Trading Volume simultaneously have a significant effect on stock prices, ROA has a positive and significant effect on stock prices. DER has no and insignificant effect on stock prices. CR has no effect and is not significant to stock prices. Stock Trading Volume has a positive and significant effect on stock prices. Keywords: ROA, DER, CR, Trade Volume, Stock Price